Models of care for improving health-related quality of life, mental health, or mortality in persons with multimorbidity: A systematic review of randomized controlled trials - Christian U Eriksen; Nina Kamstrup–Larsen; Hanne Birke; Sofie A L Helding; Nermin Ghith; John S Andersen; Anne Frølich (Journal of Multimorbidity and Comorbidity)
Objectives To categorize and examine the effectiveness regarding health-related quality of life (HRQoL), mental health, and mortality of care models for persons with multimorbidity in primary care, community care, and hospitals through a systematic review. Methods We searched PubMed, Embase, and Cochrane Central Register of Controlled Trials up to May 2020. One author screened titles and abstracts, and to validate, a second author screened 5% of the studies. Two authors independently extracted data and assessed risk of bias using the tool by the Cochrane Effective Practice and Organisation of Care group. Study inclusion criteria were (1) participants aged ≥ 18 years with multimorbidity; (2) referred to multimorbidity or two or more specific chronic conditions in the title or abstract; (3) randomized controlled design; and (4) HRQoL, mental health, or mortality as primary outcome measures. We used the Foundation Framework to categorize the models and the PRISMA-guideline for reporting. Results In this study, the first to report effectiveness of care models in patients with multimorbidity in hospital settings, we included 30 studies and 9,777 participants with multimorbidity. 12 studies were located in primary care, 9 in community care, and 9 in hospitals. HRQoL was reported as the primary outcome in 12 studies, mental health in 17 studies, and mortality in three studies—with significant improvements in 5, 14, and 2, respectively. The studies are presented according to settings. Conclusions Although 20 of the care models reported positive effects, the variations in populations, settings, model elements, and outcome measures made it difficult to conclude on which models and model elements were effective.